Character Development Analysis of Jack Dawson in Titanic Movie - Andrie Septiansyah; Risma Kartika Dewi; A. Faizin (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study examines Jack Dawson's character growth in James Cameron's 1997 film Titanic. Examining how Jack's character, morals, and behavior affect other characters especially Rose DeWitt Bukater and contribute to the story is the goal. Data were gathered from the movie's scenes, conversations, and narrative events using a qualitative descriptive method and character analysis methodology. According to the research, Jack is presented as a dynamic figure who stands for daring, optimism, independence, and selflessness. Jack maintains his moral integrity throughout the narrative while having a big impact on Rose's development from a restrained upper-class woman to an autonomous person. According to the research, Jack's relationships, choices, and reactions to social class disparities and potentially fatal circumstances all represent his growth. His ultimate sacrifice solidifies his status as a representation of human resiliency and unwavering devotion. The study comes to the conclusion that Jack Dawson's portrayal is crucial to Titanic's emotional effect and thematic complexity, especially when it comes to expressing ideas like social injustice, individual freedom, and the importance of human connection.